Femtosecond laser-induced confined microexplosion: tool for creation high-pressure phases. Issue 17 (2016) - Juodkazis, Saulius; Vailionis, Arturas; Gamaly, Eugene G.; Rapp, Ludovic; Mizeikis, Vygantas; Rode, Andrei V.
ABSTRACT: New material phases formed under non-equilibrium conditions at pressures above 100 GPa and temperatures exceeding 10 4 K, the conditions of the warm dense matter (WDM), have become accessible using micro-explosions triggered by ultra-short sub-1 ps pulses tightly focused into micro-volume with cross sections comparable with the wavelength of light. Laser-induced micro-explosions convert a material in a focal volume into a non-equilibrium disordered plasma state confined inside the bulk of pristine crystal. Ultra-high quenching rates overcome kinetic barriers to the formation of new metastable high pressure phases, which are preserved in the surrounding pristine crystal for following recovery and exploitation. Direct laser writing was used to pattern large areas by closely packed arrays of the microexplosion modified sites for structural characterisation of the minute volumes of nano-materials with transmission electron microscopy, diffraction and synchrotron X-ray diffraction. The method of ultrafast-laser induced confined microexplosion is demonstrated for modification and creation of new phases in case of bcc-Al inside sapphire, valence change of Fe-ions in olivine, formation of new tetragonal bt8 and st12 phases of silicon, Ge and O separation in GeO2 glass and molecular oxygen formation inside voids at the site of microexplosion inside glasses.